Performance in the territory of a psychosocial care center in a municipality metropolitan region of the State of Rio de Janeiro: experience report (Research, Society and Development, 2020)
The Psychosocial Care Network is composed of several health care devices that guarantee assistance to users with mental disorders, being the Primary Care Network, the Psychosocial Care Centers (CAPS). This study aimed to describe the experience of multiprofessional teams from the Psychosocial Care Centers in the territory of Rio Bonito, demonstrating all the performance and the reality of the users. This is a descriptive study, an experience report, with a qualitative approach, carried out at the Dr. Cleber Paixão Psychosocial Care Center in the city of Rio Bonito, Rio de Janeiro, Brazil, from 2013 to 2016. They were observed during the process that the division of CAPS professionals into a team by territory was a facilitator of the quality of care, contributing to the improvement of the service offered. The work in the territory was fundamental for the understanding of the user's reality, which enabled new forms of care.